Upaya meningkatkan kompetensi profesional guru dan pendampingan pengembangan media pembelajaran berbasis ramah lingkungan pada program PKM - Mario Mario; Ahmad Zaki; Muhammad Ilyas Thamrin (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The PKM program is carried out with the method of providing training and mentoring to participants regarding the development of environmentally friendly learning media to improve professional competence with the aim of (1) to increase knowledge about the development of environmentally friendly learning media, (2) participants can properly implement the development of instructional media based on environmentally friendly learning processes, and (3) participants can disseminate or disseminate knowledge of the development of environmentally friendly learning media. The main target audience for the PKM Program activities are school supervisors, school principals and school teachers in Tinggimoncong sub-district, Gowa district, South Sulawesi province. The results obtained in PKM program activities are increasing knowledge and concept of developing environmentally friendly learning media based on PKM program participants, increasing skills in developing environmentally friendly learning media based on PKM program participants, PKM program participants can make examples and arrange activities to develop environmentally friendly learning media in learning classes, and PKM program participants can implement the development of environmentally friendly learning media in learning at school. Other results obtained were increased motivation of participants in learning materials for the development of environmentally friendly learning media and high enthusiasm of participants in disseminating or disseminating the results of the PKM program, especially in the development of environmentally friendly learning media. Outputs of PKM activities are (1) increasing participant's knowledge regarding activity materials, (2) scientific articles published at national seminars, and (3) publications on PKM implementation on online media.